(untitled) (Tabanque. Revista Pedagógica, 2020)
Interculture is, by its very definition, a bridge, a reciprocal exchange between different cultures, and, in the light of this, the very delicate issue of migration, with all the corollary of increasing complexity, problems and expectations, is a a fully inter-cultural issue, which, like a highly polished mirror, presents opportunities for analysis to the alien, in relation to the changes of life they will encounter, but mainly to the natives, who see their identity relate to the unknown and distant otherness. Here, in a fully pedagogical perspective of study and analysis of intercultural education, it is precisely the relationship with the otherness that characterizes the approach with difference, which can be characterized by preconception and prejudice, when it is not openly opposed, or it can be oriented towards openness and availability towards potential enrichment.